HAK ATAS PENGADAAN DAN STANDAR RUMAH BAGI MANTAN PRESIDEN DAN/ATAU MANTAN WAKIL PRESIDEN REPUBLIK INDONESIA - Simbolon, Laurensius Arliman (Jurnal Yuridis, 2017)
President is the supreme leader in the Republic of Indonesia, it is also clearly stated in the Constitution of the Republic of Indonesia Year 1945. After the outgoing president, and became ordinary Indonesian citizens, the president is also still get one of their rights, namely the right to earn a living, it is a form of tribute to the former President or Vice President who has been leading this country during the period of his leadership. Towards the end of his term, Susilo Bambang Yudhoyono to change the rules providing a home for former president and vice president. The change was then poured in Presidential Regulation No. 52 Year 2004 on the Amendment of Presidential Decree No. 88 Year 2007 concerning Procurement and Standard Home for Former President and Vice President. The policy made by President, invited strong reactions from the public. Therefore, the facilities will be reserved for the former president and vice president in the form of procurement of the house is considered very exaggerated and does not reflect a sense of justice for the people, especially people from the lower middle class who until now have not had a home. In this paper will discuss the procurement and the right to a standard home to the former president and / or the former vice president of the republic of Indonesia, and controversy procurement and standards for the former president's home and / or former vice president of the republic of Indonesia.